PERILAKU EKONOMI MASYARAKAT MISKIN DI SEKITAR KAWASAN HUTAN GUNUNG RINJANI PULAU LOMBOK - Siddik, M. Siddik; Amiruddin, Amiruddin; Juniarsih, Nuning (Jurnal Agribisnis Indonesia, 2013)
The objectives of this research are (1) to describe behavior of household economy; (2) to analyze factors affecting the behavior of household economy; and (3) to analyze income and outcome of households on basic equilibrium level and on actual equilibrium level. The results of the research showed that the community forest programs (HKm) given to the community living around the forests had opened job opportunities and income sources to the community living around Mount Rinjani Forest, andÂ  community incomes were far above basic equilibrium level. Factors which consistently and positively affected the economic behavior of community households were the area of HKm land occupied, the diversity of household works, the access of their villages to the center of economic activities and the area of land they utilized other than HKm land. On the other hand, household incomes from government subsidies (such as BLT and Raskin) and other sources outside the thriving labor tended to make household labors became lazier and poorer, which significantly and negatively affected working time and incomes of households.